Seasonal pattern of water masses in the South China Sea - Amiruddin, Abd Muhaimin (2011)
The purpose of this study is to investigate the seasonal pattern and movement of water masses and their relation to the currents and circulations in the South China Sea (SCS). Prior studies of water masses, currents and circulations mainly focus only on the winter and summer seasons and on the deep basin of the SCS. This study is carried out over the whole SCS region for the four seasons of winter, spring, summer and fall. The hydrographic dataset from World Ocean Database 2009 is used. The dataset is processed, analyzed and visualized using the software Ocean Data View. The quality control procedure carried out comprised removal of duplicate stations,visual inspection and standard deviation checks. The data quality controlled dataset is analyzed using descriptive statistics, seasonal water mass visualization plots, seasonal variation and water mass analyses. The results indicate that seasonal variation of water mass mainly occurred in the surface layer. The sea surface temperature is generally lowest in winter and highest in summer. The sea surface salinity is highest in spring and lowest in fall. In winter, the water mass is cold and salty in the northern SCS. The cold Taiwan Strait water and salty, surface Luzon Strait water flow into the northern SCS. The Northeast Monsoon induced the intrusion of these waters into the SCS. In spring, the water mass generally becomes warmer and saltier. The inflow of surface Luzon Strait water into the SCS remains. The warm water from southern SCS propagates into the central SCS. In spring and summer, the saline SCS water intrudes into the Gulf of Thailand. During summer, the water mass is generally warmer and fresher. The warm and fresher Karimata Strait waters flow into the southern SCS. The Southwest Monsoon induced the flow of Karimata Strait water into the SCS and the flow of SCS waters into the Gulf of Thailand. In fall, the water mass cools and freshens. The Taiwan Strait water starts to intrude into northern SCS. In general, the circulation is cyclonic over the SCS basin in winter. In spring, the cyclonic circulation occupies the north and south of SCS whereas anticyclonic circulation emerged in the central SCS. During summer and fall, the circulation is cyclonic in the northern SCS whereas anticyclonic circulation occurs in the southern SCS. In conclusion, the water mass pattern in the SCS changes over the seasons in relation to the monsoon system. The surface water masses of the SCS are generally colder in winter, saltiest in spring, warmest in summer and fresher in fall. As a result of analyzing the seasonal changes over the whole year instead of only in winter and summer; it was found that in spring, there is propagation of water from the southern SCS into the central SCS. In addition, the anticyclonic circulation emerged in the central of SCS. During fall, there is start of water intrusion from Taiwan Strait into northern SCS and the retreat of Karimata Current in the southern SCS. These addition seasonal changes of water mass, currents and circulations plots can contribute to ocean climate research, marine resources management and submarine operations in the SCS.